Chronic obstructive pulmonary disease exacerbation fundamentals: Diagnosis, treatment, prevention and disease impact. Issue 6 (24th April 2021) - MacLeod, Mairi; Papi, Alberto; Contoli, Marco; Beghé, Bianca; Celli, Bartolome R.; Wedzicha, Jadwiga A.; Fabbri, Leonardo M.
Abstract: In chronic obstructive pulmonary disease (COPD), exacerbations (ECOPD), characterized by an acute deterioration in respiratory symptoms, are fundamental events impacting negatively upon disease progression, comorbidities, wellbeing and mortality. ECOPD also represent the largest component of the socioeconomic burden of COPD. ECOPDs are currently defined as acute worsening of respiratory symptoms that require additional therapy. Definitions that require worsening of dyspnoea and sputum volume/purulence assume that acute infections, especially respiratory viral infections, and/or exposure to pollutants are the main cause of ECOPD. But other factors may contribute to ECOPD, such as the exacerbation of other respiratory diseases and non‐respiratory diseases (e.g., heart failure, thromboembolism). The complexity of worsening dyspnoea has suggested a need to improve the definition of ECOPD using objective measurements such as blood counts and C‐reactive protein to improve accuracy of diagnosis and a personalized approach to management. There are three time points when we can intervene to improve outcomes: acutely, to attenuate the length and severity of an established exacerbation; in the aftermath, to prevent early recurrence and readmission, which are common, and in the long‐term, establishing preventative measures that reduce the risk of future events. Acute management includes interventions such as corticosteroids or antibiotics and measures to support the respiratory system, including non‐invasive ventilation (NIV). Current therapies are broad and better understanding of clinical phenotypes and biomarkers may help to establish a more tailored approach, for example in relation to antibiotic prescription. Other unmet needs include effective treatment for viruses, which commonly cause exacerbations. Preventing early recurrence and readmission to hospital is important and the benefits of interventions such as antibiotics or anti‐inflammatories in this period are not established. Domiciliary NIV in those patients who are persistently hypercapnic following discharge and pulmonary rehabilitation can have a positive impact. For long‐term prevention, inhaled therapy is key. Dual bronchodilators reduce exacerbation frequency but in patients with continuing exacerbations, triple therapy should be considered, especially if blood eosinophils are elevated. Other options include phosphodiesterase inhibitors and macrolide antibiotics. ECOPD are a key component of the assessment of COPD severity and future outcomes (quality of life, hospitalisations, health care resource utilization, mortality) and are a central component in pharmacological management decisions. Targeted therapies directed towards specific pathways of inflammation are being explored in exacerbation prevention, and this is a promising avenue for future research.